The main aspects of the application of educational technologies in the study process - Dromantienė, Leta; Indrašienė, Valdonė; Παγγέ, Τζένη; Bielskytė-Simanavičienė, Erika (Επιστημονική Επετηρίδα Παιδαγωγικού Τμήματος Νηπιαγωγών Πανεπιστημίου Ιωαννίνων, 2015)
Rapidly changing economic, social and political conditions, the penetration of new technologies also requires a completely different type of the university lecturers who are innovation-friendly. They must have relevant knowledge and combine didactic technologies and information and communication technologies in order that they would be able to give students an opportunity to study in an innovative and effective way. Taking into consideration that the study process is always based on a certain technology and paying attention to the shift of education paradigms, it can be established that, in the modern study process, it is extremely important to realise precisely today's educational objectives and principles which assist in implementing up-to-date educational technologies. The study is aimed at establishing what most important factors of the application of educational technologies in the process of modern studies are. The study is based on a quantitative research methodology the choice of which was determined by the newness of the analyzed problem. The study shows that the objectives of a subject of studies are always discussed with students, the latter also have an opportunity to set their own individual study objectives, they are continuously kept informed why they study concrete knowledge and what it will be needed for in the future. The creation of an environment favourable to studies is also proved by the fact that the opportunity is given to students to combine the content of their studies of a subject with their own personal experience, interests. The study process is dominated by the study process of the active creation and construction of knowledge.